Catechols and 3-hydroxypyridones as inhibitors of the DNA repair complex ERCC1-XPF. Issue 19 (1st October 2015) - Chapman, Timothy M.; Gillen, Kevin J.; Wallace, Claire; Lee, Maximillian T.; Bakrania, Preeti; Khurana, Puneet; Coombs, Peter J.; Stennett, Laura; Fox, Simon; Bureau, Emilie A.; Brownlees, Janet; Melton, David W.; et al.
Graphical abstract: Abstract: Catechol-based inhibitors of ERCC1-XPF endonuclease activity were identified from a high-throughput screen. Exploration of the structure-activity relationships within this series yielded compound13, which displayed an ERCC1-XPF IC50 of 0.6 μM, high selectivity against FEN-1 and DNase I and activity in nucleotide excision repair, cisplatin enhancement and γH2AX assays in A375 melanoma cells. Screening of fragments as potential alternatives to the catechol group revealed that 3-hydroxypyridones are able to inhibit ERCC1-XPF with high ligand efficiency, and elaboration of the hit gave compounds36 and37 which showed promising ERCC1-XPF IC50 values of <10 μM.